Analisis Kemampuan Self-Concept melalui Model Pembelajaran Kooperatif Tipe Think Talk Write pada Siswa SMP - Agus Dede Anggiana; Subaryo Subaryo; Vevi Hermawan (Symmetry: Pasundan Journal of Research in Mathematics Learning and Education, 2022)
The purpose of this study was to determine the self-concept of students who received mathematics learning using the Think Talk Write cooperative learning model better than students who received conventional learning. This research is a quasi-experimental research with nonequivalent control group research design. The population in this study were class VII students of SMPN 1 Baleendah. Sampling using purposive sampling technique. The research sample consisted of two classes, namely the control class and the experimental class. In the experimental class learning through cooperative learning model type Think Talk Write while in the control class learning using conventional learning. The data collection instrument used was a self-concept questionnaire. Data analysis using SPSS 20.0 for Windows software. The results of the study are that the Self-Concept of students who receive mathematics learning using the Think Talk Write cooperative learning model is better than students who receive conventional learning.